Mixed-method analysis of barriers to surgical care in Uganda. Issue 4 (23rd July 2020) - Incorvia, Joseph J.; Du, Robin; Tafreshi, Ali R.; Vissoci, Joao R.N.; Fuller, Anthony T.; Rice, Henry E.; Kebba, Naomi; Doshi, Pratik; Galukande, Moses; Haglund, Michael M.
Abstract : Supplemental Digital Content is available in the text. Abstract : Introduction: Barriers to surgical care in low- and middle-income countries have roots in theoretical frameworks, but are often left undefined and understudied. On the basis of the Access Evaluation Framework and Healthcare Barrier Model, this study implemented 2 consumer decision tools and a qualitative interview to elucidate significant barriers to seeking surgical care in Uganda. Methods: Participants were recruited from a convenience sample within the surgical wards of 1 national referral hospital and 1 regional referral hospital in Uganda. Individuals selected for the study answered a brief questionnaire and a ranking and rating exercise followed by an in-depth, semi-structured interview. The questionnaire evaluated demographic, economic, transportation, and care-seeking characteristics, while the ranking and rating exercises assessed potential barriers to surgical care. Descriptive statistics were used to assess characteristics of the sample. Ranking and rating medians were compared between the 2 exercises for each barrier. Results: Among the 214 participants, cost of surgery, distance to hospital, and transportation to hospital were identified as the most significant barriers to care. Language barrier, no control over decision making, and no caretaker available at the hospital were identified as the least significant barriers to care. Mulago National Referral Hospital had significantly greater costs and transportation times, indicating larger scale barriers to care than Jinja Regional Referral Hospital, even though top barriers were similar. Conclusions: Cost was the most significant barrier to surgical care among care-seekers in Uganda. Transportation to the hospital and distance from the hospital remain large barriers that need to be considered as well. These complementary analysis tools provide evidence that future policies and research need to consider mitigating cost, distance, and transportation issues for patients that need a surgical intervention. Next steps in determining more granular level differences between barriers will improve understanding on how best to address these issues.